Damage to the Fortress in Danków and Restoration of Krzepicka Gate - Drobiec, Łukasz; Drobiec, Kacper (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
This paper describes conditions of the fortress walls in Danków. Locally they were found to be in very poor condition based on site inspections and non-destructive tests. The previous main gateway to the fortress, that is, the Krzepicka Gate was in the worst condition. Hence, the restoration for the Gate and the plan for its adjustment to become the preserved ruin were prepared. The structure was restored in the years 2021-2023.
Keywords: the 17th century fortresses; curtain walls; conditions; restoration